1/2 because 7/6 & 4/3 are improper fractions(fractions that have a higher numerator than a denominator) and 3/3 should just be written as 1.
Answer:
∠ADE = ∠EDC (reason: CPCTC)
The answer to this question is
x= -2 y= 4
Answer:
Step-by-step explanation:
Essentially, begin by flipping the x and y terms:
x = (1 - 2y)^2 + 5
Then, solve for y:
![\ x = (1-2y)^2 + 5\\\sqrt{x-5} = 1 - 2y\\\sqrt{x-5} - 1 = 2y\\\frac{\sqrt{x-5} - 1}{2} = y^-1\\](https://tex.z-dn.net/?f=%5C%20x%20%3D%20%281-2y%29%5E2%20%2B%205%5C%5C%5Csqrt%7Bx-5%7D%20%3D%201%20-%202y%5C%5C%5Csqrt%7Bx-5%7D%20-%201%20%3D%202y%5C%5C%5Cfrac%7B%5Csqrt%7Bx-5%7D%20-%201%7D%7B2%7D%20%3D%20y%5E-1%5C%5C)
Because we know there is only 1 y-value for any given x-value, the inverse of the given function is also a function.